Editors' Note - David C. Thompson; Faith E. Crampton (Educational Considerations, 2012)
In this issue of Educational Considerations, we are pleased to offer readers extended, in-depth discussions of two critical issues for educational leaders and policymakers: Cost-effective factors that have the potential to improve student achievement and effective preparation programs for education leaders.